PENGARUH BEKERJA DENGAN SHIFT TERHADAP FAKTOR FISIOLOGIS PEKERJA PABRIK TRIPLEK PT. ADMIRA DI DESA BIBIS KECAMATAN SUKOMORO KABUPATEN MAGETAN TAHUN 2015 - Novyta Anggraeni .S; Trimawan Heru Wijono; Handoyo . (Poltekkes Kemenkes Surabaya, 2015)
Shift work affects the occurrence of physiological factors on workers especially night shift workers. Changes in working time from daylight to night resulted in physiological disorders.Workers can not be changed or workers circadian rhythms that are not able to adjust to changes in working time cause physiological disorders. Therefore, research on the effect of shift work on physiological factors plywood factory workers of PT. Admira rural districts Sukomoro Magetan 2015 Magetan district.This research is a descriptive study with the stratified random sampling design of 19 respondents.Based on the results of the study, 94.74% of respondents experienced a physiological disorder. Respondents who experienced a physiological disorder with symptoms of fatigue 75.93%.Male respondents who experience fatigue disorder 47.21%, 47.21% of sleep disorders, and gastrointestinal disorders 55.56%. Female respondents who experience fatigue disorder 38.89%, 27.78% of sleep disorders, and gastrointestinal disorders 27.78%. This indicates that respondents who experienced a physiological disorder that respondents can not be changed circadian rhythm,or the respondents were not able to adjust to the time change from daylight to night work. For that we need additional hour of rest and given special facilities to rest for the nightshift workers. It should also be noted the division of working time, rest periods, and the worker'sage, especially night shift workers to minimize the physiological effects of workers.